Mary as a Disciple The Reception of the Figure of Mary of Bethany (John 11:1–46) in the Old Syriac Sinaiticus Manuscript - Jutkiewicz, Piotr (2022)
The figure of Mary, Lazarus's sister, receives an enhanced role in the Old Syriac Sinaiticus translation of the raising of Lazarus (John 11:1-46). Four readings in the Syriac translation focus on Mary and consist of additions or reelaborations of the Greek text that are not errors or misunderstandings of the original but rather the result of reading the figure of Mary in the context of the Fourth Gospel as a whole. The result is a portrait of Mary of Bethany in the Sinaiticus translation that should properly be titled "portrait of a disciple." This analysis results in a deeper appreciation of the Old Syriac translator's overall interpretation of John 11.